Factors Influencing the Level of Depression in Post-Hysterectomy Women - Ni Nyoman Wariyanti; Ni Wayan Septarini; Ni Putu Widarini (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hysterectomy is one of the most commonly performed gynecological procedures to treat various conditions such as uterine fibroids, endometriosis, and malignancies. Although it can improve physical health, this procedure may lead to psychological impacts, particularly depression. So, hysterectomy can lead to depression influenced by biopsychosocial factors such as body image, social stigma, and family support, so analyzing factors associated with depression, particularly body image, among post-hysterectomy women at Sanjiwani General Hospital helps identify risks and improve psychological care for these patients. Based on this, this study aims to analyze factors associated with depression, particularly body image, among post-hysterectomy women at Sanjiwani General Hospital, Gianyar. This study used an analytical observational design with a cross-sectional approach. The sample consisted of 58 post-hysterectomy women selected using purposive sampling technique. Data were collected using the Multidimensional Body-Self Relations Questionnaire–Appearance Scales (MBSRQ-AS) to measure body image and the Depression Anxiety Stress Scale (DASS-21) to assess depression. Validity and reliability testing of these instruments were conducted prior to the study, showing that all items were valid (r-count > r-table) and reliable with a Cronbach’s alpha value > 0.70. Data analysis was performed descriptively, using the Chi-square test for bivariate analysis, and logistic regression for multivariate analysis with a significance level of 5%. Most respondents did not experience depression (67.2%), while 24.1% experienced mild depression and 8.6% experienced moderate depression. Bivariate analysis showed that body image (p=0.001), social stigma (p=0.006), and family support (p=0.002) were significantly associated with depression. Comorbidities were not significantly associated (p=0.054). Multivariate analysis showed that body image was the dominant factor influencing depression (p=0.048; OR=2.958; 95% CI: 1.011–8.658). Body image, social stigma, and family support are factors associated with depression among post-hysterectomy women, with body image being the most dominant factor.